2019
DOI: 10.9734/afsj/2019/v8i229986
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Quality and Safety of Traditional Fermented Camel Milk Product Suusac Sampled from Different Regions in North Eastern, Kenya

Abstract: Aim:The study was carried out to assess the microbial quality and safety of fermented camel milk product (Suusac) from North Eastern Kenya. Methodology: Twenty-eight samples (n=28) of Suusac from different areas of the region sold in informal markets at Eastleigh in Nairobi were aseptically collected at the sales points. The quality and safety of the Suusac with reference to selected pathogens namely E. coli, S. aureus, Shigella, and Klebsiella spp was evaluated using the standard analytical methods. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Based on technological assessment, the isolated strains Enterococcus faecium MN994352, Lactococcus lactis MN994342, and MT032418, Leuconostoc mesenteroides MT032416, MN994377, MN994378, and MT032415 hold potential as starter co-cultures for enhancing the rheological characteristics of food products [84]. [78], s2 [79], s3 [80], s4 [81]); (B) pathogenic bacteria (sources: s1 [85], s2 [86], s3 [87], s4 [88]).…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on technological assessment, the isolated strains Enterococcus faecium MN994352, Lactococcus lactis MN994342, and MT032418, Leuconostoc mesenteroides MT032416, MN994377, MN994378, and MT032415 hold potential as starter co-cultures for enhancing the rheological characteristics of food products [84]. [78], s2 [79], s3 [80], s4 [81]); (B) pathogenic bacteria (sources: s1 [85], s2 [86], s3 [87], s4 [88]).…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…Dipodascus (38.0%), Pichia (31.2%), Saccharomyces (27.9%), and Kluyveromyces (2.4%) have been found in khoormog, a fermented CM product, collected from Mongolia [106]. , s2 [79], s3 [80], s4 [81]); (B) pathogenic bacteria (sources: s1 [85], s2 [86], s3 [87], s4 [88]).…”
Section: Yeast and Moldmentioning
confidence: 99%
“…Suusac , consumed by the people of the arid and semi-arid areas of Kenya, is obtained from the spontaneous fermentation of fresh unpasteurized milk in cleaned smoke-treated gourds ( Lore et al, 2005 ). A study by Maitha et al (2019) on milk samples collected from different areas of northeastern Kenya found that suusac consumption also poses health risks to consumers. Researchers found E. coli in all samples analyzed, while Shigella spp.…”
Section: Dairy Productsmentioning
confidence: 99%
“…Each camel country has described their traditional fermented milk in terms of microbiological, physicochemical, and chemical properties, as well as volatile organic compound profiles in some cases. The most known fermented camel milk products described in the literature are shubat in Kazakhstan [ 97 ] and China [ 98 ], khoormog in Mongolia [ 99 ], garris in Sudan [ 100 , 101 ], suusac in Kenya [ 102 ], laben (lben) in Arabic countries [ 103 ], and ititu and dhanaan in Ethiopia [ 104 , 105 ] ( Table 2 ). Other traditional fermented beverages based on a mixture of camel milk and water are available in Mauritania known as zrig [ 106 ], in Morocco known as Lfrik [ 107 ], and in Iran and Turkmenistan known as chal [ 108 ].…”
Section: Fermented Milkmentioning
confidence: 99%